1996
DOI: 10.1111/j.1460-9568.1996.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nicotinic Receptor a6 Subunit mRNA is Selectively Concentrated in Catecholaminergic Nuclei of the Rat Brain

Abstract: Although the neuronal nicotinic receptor alpha 6 subunit was cloned several years ago, its functional significance remains to be investigated. Here we describe an in situ hybridization study of the mRNA for this subunit in the adult rat central nervous system using oligonucleotide probes. Specific alpha 6 mRNA labelling was restricted to a few nuclei throughout the brain; it was particularly high in several catecholaminergic nuclei [the locus coeruleus (A6), the ventral tegmental area (A10) and the substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
255
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(292 citation statements)
references
References 59 publications
33
255
4
Order By: Relevance
“…The use of other ligands such as radiolabeled nicotine, α-bungarotoxin and α-conotoxinMII has helped identify nAChR subtypes, including those containing the α4, α6 and α7 subunits [67,69,71]. These findings from receptor binding studies are in agreement with the results of in situ hybridization and RT-PCR work, which demonstrate the presence of α2 through α7 and β2 through β4 nAChR subunit transcripts in the striatum and/or substantia nigra [72][73][74][75][76][77]. The results of immunoprecipitation studies using subunit-selective nAChR antibodies suggest that the greater majority of these transcripts are translated into protein to form receptors [64,78].…”
Section: Rodentssupporting
confidence: 61%
“…The use of other ligands such as radiolabeled nicotine, α-bungarotoxin and α-conotoxinMII has helped identify nAChR subtypes, including those containing the α4, α6 and α7 subunits [67,69,71]. These findings from receptor binding studies are in agreement with the results of in situ hybridization and RT-PCR work, which demonstrate the presence of α2 through α7 and β2 through β4 nAChR subunit transcripts in the striatum and/or substantia nigra [72][73][74][75][76][77]. The results of immunoprecipitation studies using subunit-selective nAChR antibodies suggest that the greater majority of these transcripts are translated into protein to form receptors [64,78].…”
Section: Rodentssupporting
confidence: 61%
“…No signal for α2 and β4 mRNA was detected. Le Novere et al, [65] obtained virtually identical results in a study that measured in situ hybridization of the α3, α4, α5, α6, β2, β3 and β4 mRNAs in catecholamine-rich rat brain regions. These findings suggest that more than one nAChR subtype is expressed in dopaminergic neurons, but this conclusion must be treated with caution because the in situ hybridization strategies that were used in the studies discussed above lack the anatomical resolution required to determine whether specific cell types express a given mRNA.…”
mentioning
confidence: 74%
“…Some subunits are widely expressed at medium or low levels, like ␣4 and ␤2 (for the rodent, see Wada et al, 1989) while others like ␣2, ␣3, ␣6, or ␤4, are expressed at high levels yet in a limited number of structures (for the rodent, see Wada et al, 1989;Dineley-Miller and Patrick, 1992;Le Novère et al, 1996). In addition, the study of developmental patterns revealed transient mRNAs subunit expressions (such as ␣3 mRNA in the cortex, Zoli et al, 1995).…”
Section: Promoters and Regulation Of Expressionmentioning
confidence: 99%